Inovasi Es Krim Tape Sukun Dengan Penambahan Sari Kacang Gude Dan Kulit Buah Naga Sebagai Pewarna Alami - Suryandari, Esti, Dra. Aminah Asngad, M.Si (2015)
Ice cream was a dessert food product made from fats of an animal and vegetable. In this research used cow's milk, extract pigeonpea, breadfruit tape and extract dragon fruit peel. Peel of the dragon fruit containing anthocyanin can be used as natural food colour. The purpose of the research to determine the protein concentration, speed melted and organoleptic ice cream breadfruit tape. The research designed using factorial Completely Randomized Design with two factors. Factor 1 extract pigeonpea bean : cow's milk 0 : 100% (K0), 60 : 40% (K1), 50 : 50% (K2) and factor 2 peel of the dragon fruit extract 20% (P1), 15% (P2), 10% (P3). The results showed that the highest soluble protein content in K0P1 (extract pigeonpea 0%, cow's milk 100%, breadfruit tape 20%, extract dragon fruit peel 20%) to reach 0.673%. Treatment K2P2 (extract pigeonpea 50%, cow's milk 50%, breadfruit tape 20%, extract dragon fruit peel 15%) have highest melted speed during 1812.67 seconds. Ice cream with treathment K0P2 (extract pigeonpea 0%, cow's milk 100%, breadfruit tape 20%, extract dragon fruit peel 15%) has received the most preferred receptivity panelists with critceria pink colour, aroma somewhat typical tape, slightly sweet taste, texture rather soft.